Weakening processes in thrust faults: insights from the Monte Perdido thrust fault (southern Pyrenees, Spain). Issue 1 (20th December 2012) - Lacroix, B.; Leclère, H.; Buatier, M.; Fabbri, O.
Abstract The Monte Perdido thrust fault (southern Pyrenees) consists of a 6‐m‐thick interval of intensely deformed clay‐bearing rocks. The fault zone is affected by a pervasive pressure solution seam and numerous shear surfaces. Calcite extensional‐shear veins are present along the shear surfaces. The angular relationships between the two structures indicate that shear surfaces developed at a high angle (70°) to the local principal maximum stress axis σ1. Two main stages of deformation are present. The first stage corresponds to the development of calcite shear veins by a combination of shear surface reactivation and extensional mode I rupture. The second stage of deformation corresponds to chlorite precipitation along the previously reactivated shear surfaces. The pore fluid factor λ computed for the two deformation episodes indicates high fluid pressures during the Monte Perdido thrust activity. During the first stage of deformation, the reactivation of the shear surface was facilitated by a suprahydrostatic fluid pressure with a pore fluid factor λ equal to 0.89. For the second stage, the fluid pressure remained still high (with a λ value ranging between 0.77 and 0.84) even with the presence of weak chlorite along the shear surfaces. Furthermore, evidence of hydrostatic fluid pressure during calcite cement precipitation supports that incremental shear surface reactivations are correlated with cyclic fluid pressure fluctuations consistent with a fault‐valve model.